Minimal invasive fixation of distal tibial fractures does not result in rotational malalignment: A report of 24 cases with CT imaging - Sönmez, Mehmet Mesut; Gülabi, Deniz; Uğurlar, Meriç; Uzun, Metin; Sarban, Sezgin; Şeker, Ali (Turkish Trauma & Emergency Surgery, 2017)
BACKGROUND: Tibial torsion is rotation of the proximal versus the distal articular axis in the transverse plane. This study used computed tomography (CT) to examine rotational malalignment in the crus following use of minimally invasive plate osteosynthesis (MIPO) technique in distal tibial fractures and evaluated effect of rotational difference on clinical outcomes and VAS scores. METHODS: Analysis of 24 patients who were operated on for closed distal tibial fracture with MIPO technique between 2010 and 2012 was conducted. Malrotation was defined as rotational difference > 10 degrees. Operated knees were evaluated with 0.5-mm, fine-cut, 3-dimensional CT scan performed in cooperation with radiology department. Side-to-side difference in tibial torsion angle > 10 degrees was considered significant degree of malrotation. All patients were assessed clinically (visual analogue scale [VAS] and American Orthopaedic Foot and Ankle Society [AOFAS] scores) and radiologically at final visit. RESULTS: Mean follow-up period was 20.00 +/- 9.46 months (range: 18-51 months). Mean VAS score was 2.58 +/- 0.83 (range: 1-4) and mean AOFAS score was 87.50 +/- 4.05 (range: 78-93). Mean tibial rotation angle was 31.54 +/- 6.00 degrees (range: 18-45 degrees) on healthy side and 32.00 +/- 6.24 degrees (range: 10-43 degrees) on the operated side. No statistically significant difference was determined (p > 0.05). CONCLUSION: Use of intraoperative fluoroscopy, cable technique, and uninjured extremity as reference, can reduce incidence of rotational malalignment of distal tibial fractures treated with MIPO.
WOS: 000397812400011
PubMed ID: 28467582
Keywords: CT; Distal Tibia Fractures; Malrotation; MIPO